Driving the European Green Deal in Turbulent Times - Dobbs, Mary (2021)
The European Green Deal (EGD) is an ambitious strategy. However, significant events, incidents, and demands, from democratic backsliding in the EU to the Covid-19 pandemic, are causing the ground to shift underfoot. These events go beyond ordinary changes or even individual crises, cumulatively fuelling a “new normal” of turbulence for the EU, encompassing rapid, unpredictable changes. This turbulence can help and hinder policy design and implementation, requiring policy actors to think outside the box and beyond the status quo. This article investigates how the European Commission and other key actors can engage effectively with turbulence to ensure the successful delivery and implementation of the EGD. The first half of the article strengthens and adapts turbulent governance literature (Ansell & Trondal, 2018). It delineates how turbulence differs from crisis; expands the forms of turbulence to include horizontal scalar and policy turbulence, as well as its transversal attribute; and shifts the focus to governing with turbulence rather than against turbulence. The second half undertakes an initial analysis of the EGD in light of turbulence and provides a springboard for further investigations within this thematic issue and beyond. It is apparent that the EGD is both responding and contributing to a varied landscape of turbulence. Policy actors must identify and understand the sources of turbulence—including their transversal nature and the potential for responses to increase turbulence—if they are to effectively govern with turbulence.